2020
DOI: 10.1111/are.14521
|View full text |Cite
|
Sign up to set email alerts
|

Optimal background colour for rearing Asian seabass (Lates calcarifer)

Abstract: Background colour influences the growth performance and feed utilization of various fish species. In the current study, the effects of different aquarium backgrounds (transparent, white, black, red, green and blue) on growth performance, feed utilization, digestive enzyme activities, flesh quality, carcass composition and haematological parameters were investigated in Asian seabass (Lates calcarifer). The fish (16.17 ± 0.02 g initial body weight) were distributed into eighteen glass aquaria (6 treatments × 3 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 44 publications
3
13
1
Order By: Relevance
“…Although the larvae grown in white and yellow tanks in the present study showed elevated cortisol levels, they had the highest total length and survival, respectively. Similar observation was noted in Asian seabass ( Lates calcarifer ) reared in white, black and green tanks in which the fish had higher total length and survival rates despite expressing elevated cortisol levels (Santisathitkul et al, 2020). These results show that the effect of cortisol on behavioural aspects affecting growth may be dose specific.…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…Although the larvae grown in white and yellow tanks in the present study showed elevated cortisol levels, they had the highest total length and survival, respectively. Similar observation was noted in Asian seabass ( Lates calcarifer ) reared in white, black and green tanks in which the fish had higher total length and survival rates despite expressing elevated cortisol levels (Santisathitkul et al, 2020). These results show that the effect of cortisol on behavioural aspects affecting growth may be dose specific.…”
Section: Discussionsupporting
confidence: 72%
“…In the current study, we observed that crude protein, lipid, ash and moisture contents of larvae reared in tanks of different colours were significantly different. Similar results were observed in white seabream ( Diplodus sargus L.) grown in white, light blue and black tanks (Karakatsouli et al, 2007) and Asian seabass ( Lates calcarifer ) (Santisathitkul et al, 2020). However, contradictory results were observed in scaled carp ( Cyprinus carpio L) reared in black, white or green tanks (Papoutsoglou et al, 2000), beluga ( Huso huso ) reared in black, white, green, red or blue tanks (Banan et al, 2011), and thinlip mullet ( Liza ramada ) reared in black, white, green, red, yellow or blue tanks (El‐Sayed & El‐Ghobashy, 2011).…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations